Video recording as an objective assessment tool of health worker performance in neonatal resuscitation at a district hospital in Pemba, Tanzania: a feasibility study. Issue 5 (18th May 2022) - Holm-Hansen, Charlotte Carina; Poulsen, Anja; Skytte, Tine Bruhn; Stensgaard, Christina Nadia; Bech, Christine Manich; Lopes, Mads Nathaniel; Kristiansen, Mads; Kjærgaard, Jesper; Mzee, Said; Ali, Said; Ame, Shaali; Sorensen, Jette Led; et al.
Abstract : Objectives: To assess the feasibility of using video recordings of neonatal resuscitation (NR) to evaluate the quality of care in a low-resource district hospital. Design: Prospective observational feasibility study. Setting: Chake-Chake Hospital, a district hospital in Pemba, Tanzania, in April and May 2019. Participants: All delivering women and their newborns were eligible for participation. Main outcome measures: Motion-triggered cameras were mounted on resuscitation tables and provided recordings that were analysed for quality of care indicators based on the national NR algorithm. Assessment of feasibility was conducted using Bowen's 8-point framework for feasibility studies. Results: 91% (126 of 139) of women and 96% (24 of 26) of health workers were comfortable or very comfortable with the video recordings. Of 139 newborns, 8 underwent resuscitation with bag and mask ventilation. In resuscitations, heat loss prevention measures were not performed in half of the cases (four of eight), clearing the airway was not performed correctly in five of eight cases, and all newborns were suctioned vigorously and repeatedly, even when not indicated. In a quarter (two of eight) of cases, the newborn's head was not positioned correctly. Additionally, two of the eight newborns needing ventilation were not ventilated within the first minute of life. In none of the eight cases did ventilation appear to be performed effectively. Conclusions: It proved feasible to use video recordings to assess quality of care during NR in a low-resource setting, and the method was considered acceptable for the delivering women and health workers. Recordings of eight resuscitations all demonstrated deviations from NR guidelines.